Environmental and genetic parameters of growth, reproductive and survival performance of Afar and blackhead Somali sheep at Werer Agricultural Research Centre, Ethiopia - Yacob, Y. (2008)
Data collected on flocks of Afar (1976 to 1991) and Black Head Somali (1977 to 1987) at Were research center were used to study the effect of environmental factors on ewe reproductive performance, lamb survival and early growth traits (Birth, weaning, six month and yearling and pre and post-weaning daily gain) in addition genetic analyses were carried out to estimate genetic parameters (heritability, repeatability and genetic and phenotypic correlations) for early growth traits. General linear model procedures were used in the non-genetic analysis using a linear model that included the effect of year, sex, type of birth, parity, ewe age, and ewe and sire body weights at mating and their possible interactions for all traits plus regressions on age at weaning, six-month and yearling weights. AIREML procedures were used to estimate variance covariance components and genetics parameters. The results indicated that year of birth, sex, breed, type of birth and parity of dam had significant (P>0.01) effect on all early growth traits studied, except that the effect of breed on pre-weaning included in the model as a covariate was significant (P<0.01) on weaning, six-month and yearling weights. The effect of parity on post-weaning daily weight gain and weight gain from six-month to yearling was not statistically significant (P>0.05) but was only significant (P<0.001) on pre-weaning average daily weight gain. No significant interaction effect was observed. The average lamb body weights a birth, weaning, six-months and yearling weights. The effect of parity on post-weaning daily weight gain and weight gain from six-month to yearling was not statistically significant (P>0.05) but was only significant (P<0.001) on pre-weaning average daily weight gain. No significant interaction effect was observed. The average lamb body weight at birth, weaning, six-months and yearling were 2.6±0.02; 11.0±0.11 and 23.8±0.16 kg respectively. The corresponding estimates for average daily weight gain were 98.2±0.96g, 56.8±0.87g and 37.5±0.71g for birth to weaning (pre-weaning), weaning to six-months, and six-month to yearling age (post-weaning), respectively. On average, Afar lambs were significantly (P<0.001) heavier at birth, weaning, six-month and yearling and gaining more during the post weaning period than BHS lambs, although both lamb breeds had similar (P>0.05) pre-weaning growth rates. At all stages male lambs had significantly higher (P<0.001) growth rates and were consistently heavier (P<0.001) by 0.2, 1.0, 2.6 and 3.1 kg than female at birth, weaning, six-month and yearling and gained more during the post weaning period than BHS lambs, although both lamb breeds had similar (P>0.05) pre-weaning growth rates. At all stages male lambs had significantly higher (P<0.001) growth rates and were consistently heavier (P<0.001) by 0.2, 1.0, 2.6 and 3.1 kg than females at birth, weaning, six-month and yearling, respectively. Lambs born from ewes of first parity were significantly (P<0.001) lighter than those born from ewes of second to seventh parity at birth while lambs born from ewes of first and seventh parity at weaning, six-month and yearling, respectively. Lambs born as singles were significantly (P<0.001) heavier at birth weaning, six-month and yearling and gained significantly (P<0.001) more weight than their contemporary twin-born lambs respectively. Ewe fertility (ewes mated or ewes lambing, each expressed as a percentage of ewes joined) and fecundity (lambs born as a percentage of ewes joined) were significantly (P<0.001) influenced by breed of ewe, year of mating and ewe weight at mating. The effect of these sources of variations on lambing rate (ewes lambing/ewes mated) and lambing percentage (lambs born/ewe lambing) was not statistically significant (P>0.05) except, year of mating which had a highly significant (P<0.001) effect on both reproductive traits. Ewe weight at mating had no significant (P<0.005) influence on any of the reproductive traits were 71.1±1.45%, 68.8±1.50 and 71.2±1.70% for fertility1 (whether a ewe mated or not), fertlity2 (whether a ewe lambed or not) and fecundity, respectively. Afar ewes showed higher (P<0.001) reproductive performances were observed in ewes with less or equal to 20kg body weight at mating (in both breeds) as compared to ewes with body weights heavier than 20 kg. Beyond 20 kg body weight, all traits of reproductive performance increased up to the maximum point in ewes weighing 30 to 35 kg then start to decline beyond 35kg body weight except for lambing rate and lambing percentage which had consistently increased even beyond 35kg body weight. Ewe fertility and fecundity traits increased significantly for ram weight groups beyond 30 – 35 kg, reaching a peak at 35 – 40kg body weight and then started to decline beyond 40kg. Effects of breed, year of lambing, type of birth and lamb birth weight as a covariate, had a significant (P<0.001) effect on lamb survival at different stages of growth up to yearling. At all stages of growth lamb survival was not significantly affected (P>0.05) by parity of ewe or by sex of lamb, except that, the effect of sex on lambs had significantly higher (P<0.001) rate of survival than BHS lambs was 82.0±1.01% at 90 days, 78.5±1.14% at 180 days and 74.2±1.30%at 365 days of age. After lambs had significantly higher (P<0.001) rate of survival than BHS lambs at all stages up to yearling age. Although the differences in survival rate at all stages up to 270 days of age between male and female lambs were not statistically significant (P>0.05), the values were slightly higher for female lambs as compared to their contemporary males. Single born lambs had shown significantly (P<0.001) higher rate of survival at all stages up to yearling than twin born lambs. Univariate genetic analysis for afar sheep revealed that direct heritability estimates range from 0.12 to 0.37 for birth weight, 0.11 to 0.37 for weaning weight, 0.15 to 0.33 for six-month weight and 0.21 to 0.28 for yearling weight. Higher maternal heritability were obtained for birth and weaning weight than for six-month and yearling weight. Bivariate analyses was done to estimate genetic and phenotypic correlations among the various growth traits. Birth weight has sizeable genetic correlations with weaning, six-month and yearling weight. Since birth weight has significant effect on survival, selection for birth weight can bring significant improvement on overall productivity.